Analysis Of The Influence Of Electronic Word Of Mouth (E-Wom) And Social Media On Purchase Intentions Mediated By Brand Image In E-Shopping - Alya Fathur Romadhon; Ihwan Susila (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM) and social media on consumers' purchase intention in the context of e-shopping, with the mediation of brand image. The research was conducted by collecting data from respondents actively engaged in online shopping and, through appropriate statistical analysis, identifying the relationships between these variables. This research employed a quantitative approach, using questionnaires as the data collection technique. According to Sugiyono (2022:8), quantitative research is a method with the objective of testing predetermined hypotheses, using numerical data and statistical analysis in the testing process. The study provides a profound understanding of the relationships between Social Media, E-WOM, Brand Image, and Purchase Intention in the e-shopping context. It also underscores the crucial role played by Brand Image as a mediator in the influence of E-WOM and Social Media on consumers' purchasing decisions. This research can serve as a strategic guide for e-commerce businesses to enhance consumer trust and sales through better management of social media and their brand reputation.